Diversification of Lactiplantibacillus plantarum SN13T Fermented Milk Products with the Addition of Green Grass Jelly Extract (Premna oblongifolia Merr.) as a Functional Food - Syahnara, Rahmi Ayu; Yoshendri , Allisya Aulia; Melia, Sri; Juliyarsi, Indri; Sukma, Ade (Jurnal Ilmu dan Teknologi Hasil Ternak, 2025)
This study aims to deterhe the effect of adding green grass jelly extract (Premna oblongifolia Merr.) on various properties of Lactiplantibacillus plantarum SN13T fermented milk. Specifically, it exahes the impact on protein content, fat content, water content, antioxidant levels, pH, titratable acidity (TTA), total lactic acid bacterial colonies (LAB), and organoleptic values. The treatments in this study were the addition of green grass jelly extract to the fermented milk processing as much as 0%, 0.5%, 1%, and 1.5%, with each treatment repeated five times. The results showed that adding green grass jelly extract had no significant effect (p > 0.05) on protein content, fat content, moisture content, pH, TTA, total LAB colonies, and texture in the organoleptic test. However, it had a significant effect (p < 0.05) on increasing antioxidant activity and the organoleptic tests for color, aroma, and taste. Based on the results, the best addition of green grass jelly leaf extract was 1% (C), with an average antioxidant activity value of 81.38%, a color preference level of 3.08 (neutral), aroma 2.94 (neutral), taste 2.28 (somewhat disliked), and texture 3.08 (neutral). Green grass jelly leaf extract can be added to fermented milk as a functional food containing probiotics and antioxidants.